2014
DOI: 10.11648/j.pbs.20140306.16
|View full text |Cite
|
Sign up to set email alerts
|

Haptic Perception of Parallelity

Abstract: Research has shown that the haptic perception of orientation is susceptible to systematic spatial bias. Large and systematic deviations have been found in haptic parallelity matching tasks supporting a reference frame based model. It has been suggested that the observed deviations result from the use of a frame of reference that is intermediate to an allocentric and an egocentric reference frame. The systemic bias of the deviations seems be caused by the strong bias produced by the hand-centered egocentric ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
(137 reference statements)
2
16
0
Order By: Relevance
“…While the use of an allocentric reference frame would result in bars that would be perfectly parallel, the use of an egocentric reference frame would result in large differences between the orientations of both bars. The observed deviations are usually intermediate between allocentrically and egocentrically parallel and as such support a reference based model for haptic parallel matching (Van Mier 2014 ).…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…While the use of an allocentric reference frame would result in bars that would be perfectly parallel, the use of an egocentric reference frame would result in large differences between the orientations of both bars. The observed deviations are usually intermediate between allocentrically and egocentrically parallel and as such support a reference based model for haptic parallel matching (Van Mier 2014 ).…”
Section: Introductionsupporting
confidence: 73%
“…When the hands are positioned farther away from each other in the horizontal direction, the orientation of the hands is different. This suggests that the deviations in haptic parallelity matching are most likely the result of an egocentric reference frame that is biased by the hand (Kappers 2002 , 2003 ; Van Mier 2014 ). Several authors have reported results that support a hand-centered egocentric reference frame in haptic parallelity tasks (Kappers and Liefers 2012 ; Kappers and Viergever 2006 ; Van Mier 2013 ; Volcic and Kappers 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on haptic perception of orientations [5,15] includes investigations on the oblique effect [4,6,7,8] and on parallelism [10,11,13,16]. The oblique effect describes that vertical or horizontal orientations are better processed by humans than oblique orientations, such as 45 or 135 degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that humans perform better with horizontal or vertical orientations (oblique effect), we choose 90 degrees as target angle. Research about parallelism indicates that the perception of orientations is strongly biased by the hand-centered egocentric reference frame [15]. Hand orientations are insufficiently compensated and, therefore, influence the perceived orientation [13].…”
Section: Introductionmentioning
confidence: 99%